AGE AND GENDER SPECIFIC CHARACTERISTICS OF PATIENTS WITH COVID-19 IN THE AUTONOMOUS PROVINCE OF VOJVODINA IN 2020 - Tešić, Nikolina; Medić, Snežana (Medicinski podmladak, 2024)
Introduction: Clinical manifestations of coronavirus disease-2019 (COVID-19) range from asymptomatic to severe clinical forms. Factors contributing to the unfavorable disease course, including gender and age of the patients, are still being studied.The Aim: The aim of the study is to assess the age and gender specifics of patients with different COVID-19 severity in the period March - December 2020 in the Autonomous Province of Vojvodina.Material and methods: A descriptive method was applied. Data on laboratory-confirmed cases of COVID-19 were retrieved from the surveillance database of the Institute of Public Health of Vojvodina and analyzed retrospectively. In terms of disease severity, cases were classified as: asymptomatic, mild, severe or critical. The gender and age-specific characteristics of COVID-19 cases in relation to the severity of the disease were analyzed and presented in tables and graphs.Results: In the observed period, a total of 78106 COVID-19 cases were registered (incidence 4217/100,000). Female accounted for 50.8% of cases. The highest age-specific incidence was registered in the age group 30-59 years (5876/100,000). Severe and critical forms of COVID-19 were more common in patients aged ≥60 years (18.0-39.0%). The asymptomatic disease prevailed at elderly ≥ 80 years (16.0%) and children
Keywords: COVID-19; SARS-CoV-2; gender; age; disease severity